Hubungan antara Hipertensi Dalam Kehamilan (HDK), Toxemia Gravidarum dengan Kejadian BBLR Di RSUD dr. Adjidarmo Rangkasbitung Tahun 2019. - Anis Ervina; Vivi Amelia (Akademi Kebidanan La Tansa Mashiro, 2020)
The number of LBW experienced LBW in the January-August 2019 period was 17.7%, this is an increase compared to the previous year, namely in 2018, which was 14.6%. The purpose of this study was to determine the relationship between Hypertension in pregnancy and toxemia gravidarum with LBW events in RSUD Dr. Adjidarmo Rangkasbitung for the period January-August 2019. Using analytic survey methods with cross-sectional design with the population in this study were all BBL in Perinatologi Hospital Dr. Adjidarmo Rangkasbitung period the period January-August 2019 with a total of 2,729 and the number of samples taken as many as 100. The sampling technique uses simple random sampling. Data collection uses the register room of Perinatology. The results of bivariate analysis of mothers who experienced Hypertension in pregnancy gave birth to LBW by 43.8%, mothers who experienced Toxemia gravidarum gave birth to LBW by 48.8%. The history of mothers who experienced Hypertension in pregnancy obtained p value = 0.807 (p 0.05), and the history of mothers who experienced Toxemia Gravidarum obtained p value = 0.166 (p 0.05). There is no relationship between Hypertension in pregnancy and Toxemia Gravidarum with the incidence of LBW. Therefore, researchers can suggest that there are other factors that can cause LBW, such as malnutrition, age of marriage, and pregnancy spacing.